Penanggulangan Gelandangan dan Pengemis oleh Pemerintah Kabupaten Badung - Wibawa, A. A. Gd. Agung Brata; Saputra, Komang Edy Dharma; Suryana, Kadek Dedy (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2023)
One of the problems that occurs in developing countries like Indonesia is social inequality, or the increasingly widening gap in income distribution between groups, between urban and rural areas. This high poverty rate has a direct impact on the poor standard of living of people who choose to live on the streets as beggars (sprawl). As stated in regional regulations that seek to provide a deterrent effect, the Badung Regency Government continues to strive to improve supervision and control of sprawl. The government is fighting against sprawl in areas that commonly occur and disrupt public permits by carrying out efforts to prevent sprawl in Badung Regency through the Civil Service Police Unit. Based on the findings of this research, it can be said that Regional Regulation Number 7 of 2016 concerning Public Order and Community Peace is the basis for eradicating sprawl in the Badung Regency area which is very difficult to implement and is not yet functioning well. This requires support from various related parties, all levels of society in Badung Regency, as well as tourists who come to the Badung area itself.